2019
DOI: 10.1186/s40425-019-0531-2
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D signaling certifies effector CD8 T cells for memory formation

Abstract: Background The development of memory responses is an evolutionary function of the adaptive immune system. We propose that for the immune system to populate the memory compartment with the best-suited CD8 T cells it utilizes a process of certification or molecular accreditation mediated through Natural Killer Group 2D (NKG2D). This process of certification assures that the memory compartment is filled with CD8 T cells that have demonstrated their ability to kill their cognate targets through a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 59 publications
1
18
0
5
Order By: Relevance
“…Natural killer group 2 member D is a strong costimulatory receptor expressed on NK and CD8 + T cells [56]. It can transmit an activating signal in T cells, via the adaptor protein, DNAX-activating protein 10 (DAP10), leading to memory formation and enhanced inflammatory cytokine production in CD8 + T cells [57,58]. Thus, DAP10 incorporation into the 3′ end of CAR indeed improves the antitumor activity of CAR T cells against lung cancer, hepatocellular carcinoma, and gastric cancer in mouse models [59,60].…”
Section: Costimulatory Signaling Domain Optimizationmentioning
confidence: 99%
“…Natural killer group 2 member D is a strong costimulatory receptor expressed on NK and CD8 + T cells [56]. It can transmit an activating signal in T cells, via the adaptor protein, DNAX-activating protein 10 (DAP10), leading to memory formation and enhanced inflammatory cytokine production in CD8 + T cells [57,58]. Thus, DAP10 incorporation into the 3′ end of CAR indeed improves the antitumor activity of CAR T cells against lung cancer, hepatocellular carcinoma, and gastric cancer in mouse models [59,60].…”
Section: Costimulatory Signaling Domain Optimizationmentioning
confidence: 99%
“…Engagement of NKG2D on CD8 T cells in combination with IL-15 stimulation can trigger the killing of target cells, a feature of autoimmune diseases (39, 84, 95, 100-102). While NKG2D plays an important role in the effector phase of T cells, we have shown that engagement of this receptor also has longterm effects, including the promotion of memory formation (35). In the mentioned study, we show that signaling through NKG2D mediates a process that we termed memory certification.…”
Section: Nkg2d Stress Signals and T Cellsmentioning
confidence: 54%
“…Notably, studies from our group have established in animal models that NKG2D signaling also leads to the development of long-lasting CD8 T cells with enhanced cytolytic function (33)(34)(35). NKG2DL upregulation and NKG2D signaling activation in effector CD8 T cells play a role in the onset or development of some autoimmune diseases, including vitiligo, rheumatoid arthritis, celiac disease, type 1 diabetes, alopecia areata, systemic lupus erythematosus (SLE), among others (36)(37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%
“…Temporary blockade of NKG2D signaling in the effector phase resulted in development of altered defective memory CD8+ T cells, which means that uninterrupted NKG2D signaling in the effector phase promotes development of fully functional memory CD8+ T cells. This is a new feature of the NKG2D receptor [26].…”
Section: Cancers and Cancer Immunotherapymentioning
confidence: 90%